The Role of etnics in corporate governance - Zaleha Othman; Rashidah Abdul Rahman; Faridahwati Mohd Shamsudin (Penerbit Universiti Kebangsaan Malaysia, 2012)
The purpose of this paper is to explore the role of ethnics in corporate governance.The research is within an interpretive approach. The interview technique was employed to explore the issue. Interviews were conducted with 13 experts who were involved in the reform of Malaysian corporate governance. The experts were seleted based on their expertise and experience. There themes emerged in respect of the main role of ethics in corporate governance; corporate governance is a code of ethnics corporate governance is inclusive of ethics, and ethics is an affiliate of corporate governance. The research has contributed in enchaning the understanding of corporate governance by shifting the focus from a structural perspective and manages to highlight the contradictions that lie within the understandingof corporate governance in moral perspective.